O Padre Barroso e o Seminário de Macau (1860)
This 1860 diplomatic correspondence, comprising three despatches dated 25 and 26 June and 25 July, originates from the Portuguese Secretary of State for Foreign Affairs, Lynard, to António José d'Ávila J., Viscount of Mite, Minister of Her Majesty’s Government in Rome. The documents confirm receipt of multiple confidential communications from the Legation in Naples (Nos. 19, 21) and the extended series (Nos. 39, 40), along with a reserved despatch (No. 15), all concerning political developments on the Italian Peninsula during a period of significant upheaval. Central to the correspondence is the appointment of Count Alessandro Gallo as Vice-Consul of Portugal in Ancona, with instructions for the Minister to ensure the Count petitions the Ministry for the issuance of his Diplomatic Commission. Additionally, the Secretary of State transmits information relayed by Father Barroso regarding the frontier of Saint Joseph in Papo, forwarding a confidential extract to the Minister of Public Works. The despatches further request urgent clarification on colonial provisions necessary for the proposed renewal of a Commercial Treaty with Naples. These documents offer primary insight into Portugal’s diplomatic protocols, consular administration, and foreign policy considerations in mid-19th century Europe, particularly in relation to the shifting political landscape of the Italian states and colonial trade negotiations.
Keywords: Ancona; Border Relations; Colonial Affairs; Commercial Treaty Negotiations; Confidential Communications; Count Alessandro Gallo; Diplomatic Despatches; Diplomatic Protocol; Historical Document Analysis; Legation Reporting Structure; Mid-19th Century Diplomacy; Ministry of Public Works; Papo; Political Developments in Italy; Portuguese Foreign Affairs Correspondence; Portuguese Legation in Naples; Saint Joseph Frontier; Secretariat of State for Foreign Affairs; Transcription; Urgent Clarification Requests; Vice-Consul Appointment; Viscount of Mite